GC-MS ANALYSIS OF BIOACTIVE COMPONENTS FROM THE ETHANOL EXTRACT OF AVICENNIA MARINA LEAVES - Kumar, Dinesh; R, Rajakumar (Innovare Journal of Sciences, 2016)
Objectives: To investigate the phytoconstitutent of ethanol extract of Avicennia marina using GC-MS. Methods: GC-MS analysis of the leaves extract were performed using a Clarus 500 Perkin- Elmer (Auto System XL) Gas Chromatograph equipped and coupled to a mass detector Turbo mass gold – Perking Elmer Turbomas 5.2 spectrometer with an Elite-1 (100% Dimethyl ply siloxane), 300 m x 0.25 mm x 1 μm df capillary column. Results: The result of the GC-MS analysis confirmed the presence of twelve compounds. The most of the prevailing compounds are squalene ; 2R,3S-butane-1,2,3,4-tetraol; Palmitic acid; Hexadecanoic acid, ethyl ester; 3,7,11,15-Tetramethyl-2-hexadecen-1ol; Phytol; (E)-9-Octadecenoic acid ethyl ester; Dodecanoic acid; Octadecanoic acid, 2-methyl-,methyl ester; 3Cyclohexen-1 carboxaldehyde,3-methyl; cis-9-Hexadecenal; 3,7-dimethyl-2, 6-octadienyl ester etc. Conclusion: This study concluded that the plant leaves contains rich amount of phytoconstituents. These bioactive components are very useful to cure many diseases and also used in many pharmaceutical industries. Keywords: Avicennia marina, GC-MS, Bioactive compounds.